1998
DOI: 10.1002/(sici)1097-0142(19980201)82:3<531::aid-cncr15>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

A five-alpha reductase inhibitor or an antiandrogen prevents the progression of microscopic prostate carcinoma to macroscopic carcinoma in rats

Abstract: of 5-alpha reductase inhibitor (e.g., finasteride) and a pure antiandrogen (e.g., Hideyuki Akaza 1 casodex) on rat prostate carcinogenesis and to determine whether latent prostate Mizuki Onozawa 1 carcinoma can be prevented to develop to clinically significant cancer by use of Tomoyuki Shirai 2 these drugs. Yukitaka Ideyama 3 METHODS. F344 rats were subcutaneously administered 3,2-dimethyl-4-aminobi-phenyl (DMAB) for the first 20 weeks and testosterone propionate throughout the 1 Department of Urology, Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…TRAP lesions have many advantages, for example, their large size allows adequate materials to be obtained and development of prostate cancer occurs in a shorter experimental period and more efficiently compared with several other rat prostate carcinogenesis models. [11][12][13][14][15][16][17][18][19] These characteristics of TRAP may make it particularly suitable for evaluation of strategies for chemoprevention and treatment. The present study was conducted to assess whether finasteride and flutamide have the ability to suppress prostate carcinogenesis in our TRAP model.…”
Section: Introductionmentioning
confidence: 99%
“…TRAP lesions have many advantages, for example, their large size allows adequate materials to be obtained and development of prostate cancer occurs in a shorter experimental period and more efficiently compared with several other rat prostate carcinogenesis models. [11][12][13][14][15][16][17][18][19] These characteristics of TRAP may make it particularly suitable for evaluation of strategies for chemoprevention and treatment. The present study was conducted to assess whether finasteride and flutamide have the ability to suppress prostate carcinogenesis in our TRAP model.…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation might be understaging of prostate cancer at initial diagnosis. 6 Another interesting aspect in our patient's case was her moderate response to anti-androgens (flutamide), which may suggest the existence of an active androgen receptor (AR) pathway. Few studies have shown that AR is commonly expressed in prostate cancer with increased levels after androgen deprivation.…”
Section: Discussionmentioning
confidence: 92%
“…There are some experimental data suggesting that chemoprevention may decrease the risk of prostate cancer (Tsukamoto et al, 1998). Also studies on the use of 5-alpha reductase treatment in chemoprevention of prostate cancer are ongoing (Brawley and Parnes, 2000).…”
Section: Clinical Management and Counseling Of Patients With A Genetimentioning
confidence: 99%